Keefektifan Media Video Animasi untuk Meningkatkan Minat Dan Hasil Belajar Mata Pelajaran IPAS Kelas IV SD Negeri Klumprit 01 Nusawungu Kabupaten Cilacap - Lavenia Ayu Caella; Sigit Yulianto (Postgraduate, University of Mataram, 2024)
The science and science learning implemented at SD Negeri Klumprit 01 Nusawungu, Cilacap Regency still uses conventional media, which results in a lack of student interest in learning and has an impact on student learning outcomes. One learning media that can attract students' interest in participating in the learning process is animated video media. The aim of this research is to analyze and describe effective learning media to increase interest and learning outcomes in science subjects. This type of research is quantitative experiment, with A quasi-experimental Design and a Nonequivalent Control Group Design. The population members consisted of class IVA as the control class and class IVB as the experimental class. The data collection techniques used were tests and questionnaire sheets. Data analysis in this research used the Independent Sample T Test to test the differences and effectiveness of Animation Video Media. The research results show that the application of animated video media is more effective than conventional media. The results of the analysis of learning interest and learning outcomes show that the experimental class has a higher average interest score (82.03) compared to the control class (75.88). Meanwhile, the average learning outcome score for the experimental class was higher (81.38) than the control class (66.15). It was concluded that the application of animated video media was more effective than conventional media in the science and sciences subject on Building a Civilized Society.